2012
DOI: 10.3390/insects3010200
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Conifer-Infesting Bark Beetles and Fungi in Fennoscandia

Abstract: Bark beetles (Coleoptera, Scolytinae) have a widespread association with fungi, especially with ophiostomatoid fungi (Ascomycota) that cause blue staining of wood, and in some cases, serious tree diseases. In Fennoscandia, most studies of these fungi have focused on economically important bark beetle species and this is likely to have led to a biased view of the fungal biodiversity in the region. Recently, the associations between fungi and bark beetles in Fennoscandia have been shown to be more diverse than p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
64
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(68 citation statements)
references
References 88 publications
(338 reference statements)
4
64
0
Order By: Relevance
“…Several studies have reported associations between conifer-and hardwood-infesting bark beetles and species of the Ophiostomatales in Poland (e.g. Jankowiak et al, 2017Jankowiak et al, , 2019 and other European countries (Kirisits, 2004;Linnakoski et al, 2012). However, relatively little is known regarding wound-associated Ophiostomatales in European hardwood ecosystems.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported associations between conifer-and hardwood-infesting bark beetles and species of the Ophiostomatales in Poland (e.g. Jankowiak et al, 2017Jankowiak et al, , 2019 and other European countries (Kirisits, 2004;Linnakoski et al, 2012). However, relatively little is known regarding wound-associated Ophiostomatales in European hardwood ecosystems.…”
Section: Introductionmentioning
confidence: 99%
“…Bark and ambrosia beetles (Curculionidae, Scolytinae) are economically and ecologically important pests of trees in urban, forest, plantation and agricultural settings (Avtzis et al 2012;Harrington 2005;Kirisits 2004;Paine et al 1997;Six & Wingfield 2011), with about 225 genera and more than 6 000 described species globally (Avtzis et al 2012;Linnakoski et al 2012). Some, like the southern pine bark beetle (SPB), Dendroctonus frontalis Zimmermann, are capable of killing healthy trees, and causes substantial financial losses (Price et al 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Scolytine beetles usually have complex associations with various organisms, including fungi (Linnakoski et al 2012;Six & Paine 1998;Six & Wingfield 2011;Whitney 1982), bacteria (Bridges 1984), mites (Cardoza et al 2008;Klepzig et al 2001;Moser et al 1995Moser et al , 2005 and nematodes (Cardoza et al 2008;Moser et al 2005). Those associated with ophiostomatoid fungi (e.g., species of Ceratocystis, Ophiostoma and Raffaelea) are of particular interest, as these fungi include important tree pathogens (Klepzig et al 2001;Moser et al 1995;Wood 1982).…”
Section: Introductionmentioning
confidence: 99%
“…Outbreaks and damage to timber and to other forest products are typical for few species, but have nevertheless made these beetles known to a broader audience (Linnakoski et al, 2012).…”
Section: Bark and Ambrosia Beetlesmentioning
confidence: 99%